Test Assessment, Due Motivation and Legal Intellectual Capital, 2012- 2022 - Flores Arocutipa, Javier Pedro (2024)
The investigation aims to verify a relationship between better evidence assessment and due motivation in the legal intellectual capital in Peru, 2012 -2022. It is primary research, not an experiential design, and a relational, quantitative approach through the observation method in this research. The sample, 47 files, evaluated 122 magistrates of prosecutors and judges with file, experience and training according to information published on the portal of the National Superintendence of Higher Education University (SUNEDU), National Institute of Statistics and Informatics (INEI) and National Council of Science, Technology and Technological Innovation (CONCYTEC), interviewed 136 procedural subjects with a questionnaire of 17 questions, the results revealed nullity of 47 records by default of motivation, affectation of the due process through defective evidentiary assessment, showed a positive correlation between the failure to provide adequate written justification in the jurisdictional field with a Chi-square value of 47,785, and a sig. 0.000. It is concluded that there is correspondence between better intellectual capital of judges and assessment of evidence and motivation.